Perkembangan Kajian Astronomi Islam Di Alam Melayu - Azhari, Susiknan (Jurnal Fiqh, 2010)
Nowadays, the presence of Islamic astronomy is very important because in some ways it still needed by Muslim countries. Therefore, this article attempts to elaborate the recent development of Islamic astronomy in the Malay world especially in Indonesia and Malaysia. This article also will describe the contribution of early figures i.e. Ahmad al-Fathani and Sheikh Tahir Jalaluddin. For the future needs aims to build mutually beneficial cooperation between Indonesia and Malaysia in order to promote the Islamic astronomy in the world.